ProNGF increases breast tumor aggressiveness through functional association of TrkA with EphA2. (1st May 2019) - Lévêque, Romain; Corbet, Cyril; Aubert, Léo; Guilbert, Matthieu; Lagadec, Chann; Adriaenssens, Eric; Duval, Jérémy; Finetti, Pascal; Birnbaum, Daniel; Magné, Nicolas; Chopin, Valérie; Bertucci, François; et al.
Abstract: ProNGF expression has been linked to several types of cancers including breast cancer, and we have previously shown that proNGF stimulates breast cancer invasion in an autocrine manner through membrane receptors sortilin and TrkA. However, little is known regarding TrkA-associated protein partners upon proNGF stimulation. By proteomic analysis and proximity ligation assays, we found that proNGF binding to sortilin induced sequential formation of the functional sortilin/TrkA/EphA2 complex, leading to TrkA-phosphorylation dependent Akt activation and EphA2-dependent Src activation. EphA2 inhibition using siRNA approach abolished proNGF-stimulated clonogenic growth of breast cancer cell lines. Combinatorial targeting of TrkA and EphA2 dramatically reduced colony formation in vitro, primary tumor growth and metastatic dissemination towards the brain in vivo . Finally, proximity ligation assay in breast tumor samples revealed that increased TrkA/EphA2 proximity ligation assay signals were correlated with a decrease of overall survival in patients. All together, these data point out the importance of TrkA/EphA2 functional association in proNGF-induced tumor promoting effects, and provide a rationale to target proNGF/TrkA/EphA2 axis by alternative methods other than the simple use of tyrosine kinase inhibitors in breast cancer. Highlights: EphA2 is a key element of proNGF signaling in breast cancer cells. ProNGF-induced Src activation through EphA2 is independent of TrkA phosphorylation. TrkA/EphA2 PLA signal is associated with decrease of overall survival in breast cancer.